Challenges and Recent Advances in High Capacity Li‐Rich Cathode Materials for High Energy Density Lithium‐Ion Batteries (Adv. Mater. 50/2021). Issue 50 (13th December 2021) - He, Wei; Guo, Weibin; Wu, Hualong; Lin, Liang; Liu, Qun; Han, Xiao; Xie, Qingshui; Liu, Pengfei; Zheng, Hongfei; Wang, Laisen; Yu, Xiqian; Peng, Dong‐Liang
Abstract : Li‐Rich Cathode Materials In article number 2005937, Qingshui Xie, Xiqian Yu, Dong‐Liang Peng, and co‐workers review the recent challenges and prospects in Li‐rich cathode materials, and the recent understanding of the complex relationships between inherent material issues and external performance degradation. The proposed future opportunities will benefit the practical applications of Li‐rich cathode materials.